PENGARUH KUALITAS PELAYANAN PAJAK, SANKSI PAJAK DAN PENGETAHUAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KANTOR PELAYANAN PAJAK PRATAMA KUPANG - Vicsan Margesti Yonita Mooy (Globalwriting Academica Consulting & Publishing, 2022)
This study aims to determine the effect of tax service quality, tax sanctions and tax knowledge on individual taxpayer compliance at the Pratama Kupang Tax Service Office. The population of this study is individual taxpayers registered at the Pratama Kupang Tax Service Office in 2016-2020. The sampling method in this study used the incidental sampling method with the Slovin formula as many as 100 individual taxpayers. The primary data collection technique used is a survey technique using an ordinal scale questionnaire. The data analysis technique used is multiple linear regression and statistical tests using the SPSS version 26 application program. The results of this study indicate that, 1) the quality of tax services affects individual taxpayer compliance, 2) tax sanctions affect individual taxpayer compliance, 3) tax knowledge has no effect on individual taxpayer compliance, and 4) tax service quality, tax sanctions and tax knowledge simultaneously affect individual taxpayer compliance.